SYNTHESIS AND PHOTOLUMINESCENCE STUDIES ON ZINC OXIDE NANOWIRES - Nguyen Ngoc Long; Ngo Xuan Dai; Nguyen Thi Thuc Hien (Universitas Gadjah Mada, 2007)
Semiconductor single crystal ZnO nanowires have been successfully synthesized by a simple method based on thermal evaporation of ZnO powders mixed with graphite. Metallic catalysts, carrying gases, and vacuum conditions are not necessary. The x-ray diffraction (XRD) analysis shows that the ZnO nanowires are highly crystallized and have a typical wurtzite hexagonal structure with lattice constants a = 0.3246 nm and c = 0.5203 nm. The scanning electron microscopy (SEM) images of nanowires indicate that diameters of the ZnO nanowires normally range from 100 to 300 nm and their lengths are several tens of micrometers. Photoluminescence (PL) and photoluminescence excitation (PLE) spectra of the nanowires were measured in the range of temperature from 15 K to the room temperature. Photoluminescence spectra at low temperatures exhibit a group of ultraviolet (UV) narrow peaks in the region 368 nm 390 nm, and a blue-green very broad peak at 500 nm. Origin of the emission lines in PL spectra and the lines in PLE spectra is discussed.